Cultivating profitable and nutritious tomatoes: Tips for success in Bangladesh. A brief guide on how to grow better tomatoes - Rahaman, Md. Arifur; Cheesman, Stephanie; Parupalli, Bharathi; Hossain, Md. Shakhawat; Ferdous, Zannatul; Huda, Md. Shamsul; Krupnik, Timothy J. (TAFSSA, 2023)
Tomatoes (Solanum lycopersicum) are known for their nutritional value, boasting high levels of vitamin A, vitamin C, and antioxidants. In addition to these benefits, tomatoes can be highly profitable for farmers who have access to markets. Ensuring a successful tomato crop and maximizing yield however hinges on the quality of seedlings and season-long management practices. Whether sourced from commercial nurseries or grown on-farm, good farm management should place emphasis on seedling establishment to enhance tomato productivity. This brief provides basic advice on how to better manage tomato production in Bangladesh’s unique agroecosystems.